2010
DOI: 10.1016/j.proeng.2010.09.063
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive catalytic gas sensor for hydrogen detection based on sputtered nanoporous platinum

Abstract: This paper presents a new thermal gas sensor for hydrogen detection based on a catalytic thin film made of sputtered nanoporous platinum. Due to an increased porosity of sputtered catalytic layers, sensitivity could remarkably be raised from commonly 6 V/ppm [1] up to 18 V/ppm. As sensing element a thermopile made of p-doped polysilicon and an alloy of tungsten titanium is used. A second thermopile is placed for reference measurement and reduced cross sensitivity on same membrane

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
10
0
2
Order By: Relevance
“…In 2001, Shin et al [420] designed a thick film NiO-based H 2 sensor (Figure 16a), in which a half surface coated by a Pt thin layer is acting as catalyst, reacting with H 2 and releasing heat, creating a hot region so that a TE voltage can form across the hot and cold region of the film to indicate the existence of H 2 . Such film gas sensors have shown sufficient sensitivity and short response time, [421] Adv. Energy Mater.…”
Section: Te Gas Sensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2001, Shin et al [420] designed a thick film NiO-based H 2 sensor (Figure 16a), in which a half surface coated by a Pt thin layer is acting as catalyst, reacting with H 2 and releasing heat, creating a hot region so that a TE voltage can form across the hot and cold region of the film to indicate the existence of H 2 . Such film gas sensors have shown sufficient sensitivity and short response time, [421] Adv. Energy Mater.…”
Section: Te Gas Sensorsmentioning
confidence: 99%
“…[420] Thick film NiO-based H 2 sensors have also been investigated via Li doping and using different oxide layers [422] and substrates, [423] which show reasonable sensing properties at room temperature with noise-free voltage signals. [421] Moreover, a double AuPtPd/SnO 2 and Pt/Al 2 O 3 catalyst [428] and Au/SnO 2 -Co 3 O 4 [429] (Figure 16b,c) on a micro-TE sensor was used for CO gas sensing; porous alumina-based sensors were developed for hydrocarbon; [430] dual-catalyzed Pd/θ-Al 2 O 3 and Pt/α-Al 2 O 3 system were able to detect H 2 and CH 4 , [431] which can be used in monitoring the combustion of fuel gas in industrial furnaces. [421] Moreover, a double AuPtPd/SnO 2 and Pt/Al 2 O 3 catalyst [428] and Au/SnO 2 -Co 3 O 4 [429] (Figure 16b,c) on a micro-TE sensor was used for CO gas sensing; porous alumina-based sensors were developed for hydrocarbon; [430] dual-catalyzed Pd/θ-Al 2 O 3 and Pt/α-Al 2 O 3 system were able to detect H 2 and CH 4 , [431] which can be used in monitoring the combustion of fuel gas in industrial furnaces.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 2 more Smart Citations
“…It was only after a while, that Sturm et al reported about a thermoelectric combustible gas sensor again. It showed improved sensitivity as sputtered nonporous platinum thin films were used as catalyst [ 12 ]. More recently, researchers have started using catalysts made from metal nanoparticles and thereby initiated a new era in gas sensing technology with high sensitivity and low power consumption [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%